Organization of the Lesson Process on the Basis of Innovative Educational Technologies in Geography - Hayitovna, Aslanova Feruza (Universitas Muhammadiyah Sidoarjo, 2022)
this article provides information on the establishment of a modern and innovative educational environment in the teaching of geography science. Geographical education is said to be a reliable basis for studying countries and the planet.Sufficient recommendations have been made to increase efficiency in geography.